2017 IEEE International Joint Conference on Biometrics (IJCB) 2017
DOI: 10.1109/btas.2017.8272687
|View full text |Cite
|
Sign up to set email alerts
|

Generative adversarial network-based synthesis of visible faces from polarimetrie thermal faces

Abstract: The large domain discrepancy between faces captured in polarimetric (or conventional) thermal and visible domain makes cross-domain face recognition quite a challenging problem for both human-examiners and computer vision algorithms. Previous approaches utilize a two-step procedure (visible feature estimation and visible image reconstruction) to synthesize the visible image given the corresponding polarimetric thermal image. However, these are regarded as two disjoint steps and hence may hinder the performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 31 publications
0
93
0
Order By: Relevance
“…Regarding Protocol I, we evaluate and compare the performance of the proposed method with recent state-of-theart methods [35,19,27,26,5,36]. Figure 5 shows the evaluation performance for two different experimental settings, S0 (representing conventional thermal) and Polar separately.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding Protocol I, we evaluate and compare the performance of the proposed method with recent state-of-theart methods [35,19,27,26,5,36]. Figure 5 shows the evaluation performance for two different experimental settings, S0 (representing conventional thermal) and Polar separately.…”
Section: Comparison With State-of-the-art Methodsmentioning
confidence: 99%
“…It has been shown that polarimetric thermal imaging captures additional geometric and textural facial details compared to conventional thermal imaging [10]. Hence, the polarization-state information has been used to improve the performance of cross-spectrum face recognition [10,27,30,35,26,5]. A polarimetric, referred to as Stokes images, is composed of three channels: S0, S1 and S2.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations